PELAKSANAAN DUI’ PANAIK DALAM PERNIKAHAN ADAT BUGIS DI DESA RIAK SIABUN I SUKARAJA KABUPATEN SELUMA - Fitri Riskiyah (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2018)
The purpose of this research is to investigate the implementation of Dui „Panaik in Bugis traditional wedding and to analyze it from the perspective of Islamic law in Riak Siabun 1 Village, Sukaraja sub-district of Seluma. This research is a field research that means the data collention was conducted directly in the field, in order to support this kind of reasearch which also in the form of descriptive qualitative study. Then, the data collecting techniques used are: observation, documentation, interview. The finding of this study showed that the implementation of Dui „Panaik in the Bugis traditional wedding takes place after the acceptance of the proposal, starting from the review (Mammanu‟manu‟), proposal appointment (Massuro, Madduta), acceptance of the proposal (Mappetu „Ada), and the passing on of Dui „Panaik by preparing the brideprice at the groom‟s house which is covered with a double-stranded white cloth, tied around the neck of one of the men who still has a close relationship or family status. The result of the study of Dui „Panaik in the perspective of Islamic law is that in Islamic law only dictates the groom to pay the dowry, it is also advisable to the bride not to ask for excessive wedding gift. Islam also does not regulate nor prohibit the provisions of Dui „Panaik in Bugis traditional marriage because there is no explicit proof, but the most essential thing is that giving Du‟i‟ Panaik does not oppose with shari‟ah, because the determination of Dui „Panaik has no element of compul- sion because it is done by deliberation and has become a good habit („Urf Shahih), which is a custom that is maintained by the society, and as long as it is not againts with aqidah and shari‟ah then it is permitted, as in the rule of fiqhiyah.